Thermogravimetric Study on Decomposition Rate of Ammonium Nitrate Under Effect of Chromium Containing Catalysts - Pandey, M.; Jha, S.; Jha, A.; Jha, R.R. (Asian Journal of Chemistry, 2010)
The catalytic influence of chromium based catalyst on thermal degradation of pure ammonium nitrate has been analyzed through thermogravimetric analyses in a temperature range from ambient to 350 ºC. The TGA results reveal that all the additives alter the degradation rate and activation energy. The TGA thermograms show that in case of chromium oxide (CrO3), ammonium dichromate and potassium dichromate catalyzed ammonium nitrate system degradation start at earlier temperature with respect of pure ammonium nitrate degradation where as in case of lead chromate and copper chromate, initially degradation is get delayed but in all cases it completed at lower temperature. Delay in degradation is correlated with the ionic size of cation and melting point of each catalyst. Further activation energy of various ammonium nitrateadditive systems have also been found to alter significantly in comparison to pure ammonium nitrate (31.31 kcal/mol) where lower value in all systems except with copper chromate-ammonium nitrate system (31.909 kcal/mol). There appears to be a clear link between the ionic radii of cations of chromate/dichromate additives and their efficacy in enhancing the decomposition process of ammonium nitrate. A plausible mechanism has been proposed.